Rethinking English Studies Through AI: Challenges, Ethics, and Innovation - Tomaž Onič; Mladen Borovič; David Hazemali (ELOPE, 2025)
Over a relatively brief period, the rapid development of artificial intelligence (AI) has reshaped our perception of traditional concepts that have been with us for decades, some even for centuries. Communication, language, academic writing, translation, and education have not escaped that transformation. Generative AI tools, particularly chatbots that use large language models (LLMs) to generate tailor-made texts, presentations, images, and videos, have entered the classroom, academic research, and various professional settings – often faster than our pedagogical frameworks and ethical standards can adapt.